The AWARENESS FROM ANIMAL AND HUMAN FOUND IN A WHALE'S TALE SHORT MOVIE - Ni Made Dwi Murtami; I Made Perdana Skolastika (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
This research intends to find out the character of a whale and other animal characters saving the ocean in A Whales Tale short movie. A Whales Tale is an animated movie that delivers a story of animal life in the ocean; therefore, it is interesting to explore those stories because a lot of animals trying to help and keep the ocean a safe place to live. Thus, for that, this research focuses on what the action or activities done by the animal indicated to the environment, especially in the ocean, and is related to ecocriticism theory that needs to be interpreted. Appearing in interpreting ecocriticism, this research utilizes Greg Garrard-related ecocriticism theories which relate to the key concept are pollution and animal. This research applied qualitative methods. It is found that the whales and other living things in the ocean take care of all around them. An animal or a whale normally just receive what human make for the environment but in this short movie, the animal character also joins to keep everything in a good condition so the world balance. Therefore, the movie attempts to give awareness about the ocean about the environment. In the end, it is expected that this research may create more respect and responsibility for plastic which is bad for the earth and affect a lot of stuff on this planet.